Medicinal plants used by local communities in southern Fars Province, Iran - Saeideh Ghafouri; Roja Safaeian; Gholamabbas Ghanbarian; Thea Lautenschläger; Ehsan Ghafouri (Scientific Reports)
Abstract Medicinal plants hold immense potential for drug discovery, with indigenous knowledge being crucial for their identification and utilization. This study investigated medicinal plant use in rural communities of Lar, Gerash, and Lamerd counties, southern Iran. A total of 200 respondents from three ethnic groups in 27 local communities were interviewed over a two-year period (2020–2022) and the data was analyzed using the ethnobotanyR package in R software. Quantitative ethnobotanical indices including (FC), (FL), (RFC), (ICF), (UR), (UV), (CI), (CVs), (CV), (FUV), and (PPV) were calculated. The conservation status of the plants was assessed based on the IUCN Red List. A total of 171 plant species from 53 families were documented, with Lamiaceae and Fabaceae being the most common. Leaves were the most utilized plant part in the preparation of medicines. Decoction was the most prevalent method of preparation, and oral administration was the most common route of consumption. Gastrointestinal diseases have the highest ICF value. Notably, the study documented new medicinal applications for 70 plant species, expanding the region’s ethnobotanical knowledge. The study highlights the need for documenting and disseminating traditional knowledge, as it provides fundamental data for further research and conservation efforts.